Embracing the darkness : a cultural history of witchcraft - Callow, John, Ph. D. (London : I.B. Tauris, 2018)
A belief in the supernatural, and in black magic, has been central to European cultural life for 3,000 years. From the German witch trials to the macabre novels of Dennis Wheatley; from the sadistic persecution of eccentric village women to the seductive sorceresses of TV's Charmed; and from Derek Jarman's baroque film sets and punk vision to Ken Russell's The Devils, John Callow brings the world of the witch, mage and necromancer to life. Witchcraft has profoundly shaped the Western imagination, and endures in the forms of modern-day Wicca and Paganism. This book is an account of this aspect of the Western cultural experience.
The figure at the window -- The witch house of Bamberg -- The widow, the fish and the enchanted goatskins -- A nightmare given form -- The brutalised witch -- Little Sister Jeanne of the Angels -- I shall go unto a hare -- The flight of the witch : from reason to romance -- The witch on the Barbican -- The way through the woods.
Includes bibliographical references (pages 249-253) and index.
Keywords: Witchcraft -- History; Magic -- History; Occultism -- History; History